Effectiveness of prayer in reducing anxiety in cancer patients - Carvalho, Camila Csizmar; Chaves, Erika de Cássia Lopes; Iunes, Denise Hollanda; Simão, Talita Prado; Grasselli, Cristiane da Silva Marciano; Braga, Cristiane Giffoni (Revista da Escola de Enfermagem da USP, 2014)
Objective: To evaluate the effect of prayer on anxiety in cancer patients undergoing chemotherapy. Method: Quasi-experimental study, with pre and post-intervention. Twenty patients admitted to treatment of continuous intravenous chemotherapy were recruited. The volunteers were evaluated through interviews using a questionnaire of sociodemographic, clinical and spiritual characteristics, the Index of Religiosity Duke University and the State-Trait Anxiety Inventory. Vital signs were measured and collected salivary cortisol. The intervention was applied prayer and data collection occurred in three phases: first collection (baseline), pre and post-intervention. Results: The data found between the pre and post-intervention samples showed different statistically significant for state anxiety (p=